Effect of maternal supplementation with vitamin E on the concentration of α-tocopherol in colostrum - Larisse Rayanne Miranda de Melo; Heleni Aires Clemente; Dalila Fernandes Bezerra; Raquel Costa Silva Dantas; Héryka Myrna Maia Ramalho; Roberto Dimenstein (Elsevier, 2017)
Objective: To evaluate the effect of maternal supplementation with vitamin E on the concentration of α-tocopherol in colostrum and its supply to the newborn. Method: This randomized clinical trial enrolled 99 healthy adult pregnant women; of these, 39 were assigned to the control group and 60 to the supplemented group. After an overnight fast, 5 mL of blood and 2 mL of colostrum were collected. After the first sampling (0 h milk), the supplemented group received 400 IU of supplementary vitamin E. Another 2 mL milk aliquot was collected in both groups 24 h after supplementation (24 h milk). The samples were analyzed by high-performance liquid chromatography. The α-tocopherol content provided by colostrum was calculated by considering a daily intake of 396 mL of milk and comparing the resulting value to the recommended daily intake for infants aged 0-6 months (4 mg/day). Results: The initial mean concentration of α-tocopherol in colostrum was 1509.3 ± 793.7 μg/dL in the control group and 1452.9 ± 808.6 μg/dL in the supplemented group. After 24 h, the mean α-tocopherol concentration was 1650.6 ± 968.7 μg/dL in the control group (p > 0.05) and 2346.9 ± 1203.2 μg/dL in the supplemented group (p < 0.001), increasing the vitamin E supply to the newborn to 9.3 mg/day. Initially, 18 women in the supplemented group provided colostrum α-tocopherol contents below 4 mg/day; after supplementation only six continued to provide less than the recommended amount. Conclusion: Maternal vitamin E supplementation increases the supply of the vitamin to the infant by providing more than twice the Recommended Daily Intake. Resumo: Objetivo: Avaliar o efeito da suplementação materna com vitamina E sobre a concentração de α-tocoferol no colostro e o fornecimento desta para o recém-nascido. Método: O estudo clínico randomizado foi realizado com 99 parturientes adultas e saudáveis, sendo 39 alocadas no grupo controle e 60 no grupo suplementado. Após jejum noturno, foram coletadas 5 mL de sangue e 2 mL de colostro das parturientes. Após a primeira coleta (leite 0 h), o grupo suplementado recebeu suplementação com 400 UI de vitamina E. Foi realizada nova coleta de 2 mL de colostro, em ambos os grupos, 24 h após a suplementação (leite 24 h). As amostras foram analisadas por Cromatografia Líquida de Alta Eficiência. A quantidade de α-tocoferol fornecida pelo colostro foi considerada para uma ingestão diária de 396 mL de leite e comparada com a Ingestão Diária Recomendada para crianças de 0 a 6 meses (4 mg/dia). Resultados: A concentração média inicial de α-tocoferol no colostro foi 1509,3 ± 793,7 μg/dL no grupo controle e 1452,9 ± 808,6 μg/dL no grupo suplementado. Após 24 horas a concentração média de α-tocoferol no grupo controle foi 1650,6 ± 968,7 μg/dL (p > 0,05), já no grupo suplementado a concentração média foi 2346,9 ± 1203,2 μg/dL (p < 0,001), aumentando assim a oferta de vitamina E para o recém-nascido para 9,3 mg/dia. Inicialmente 18 mulheres do grupo suplementado forneciam valores inferiores a 4 mg/dia de α-tocoferol em seu colostro, após suplementação apenas 6 continuaram a fornecer quantidade inferior ao recomendado. Conclusão: A suplementação materna com vitamina E promove o aumento do fornecimento da vitamina para o recém-nascido, fornecendo mais do que o dobroda Ingestão Diária Recomendada. Keywords: Maternal supplementation, Vitamin E, Alpha-tocopherol, Nutritional needs, Newborn, Human colostrum, Palavras-chave: Suplementação materna, Vitamina E, Alfa-tocoferol, Requerimento nutricional, Recém-nascido, Colostro humano